Application of Electrical Resistivity Method to Site Characterisation for Construction Purposes at Institute of Agriculture Research and Training Moor Plantation Ibadan - Babatunde A. Adebo; Oladipupo Emmanuel Makinde; Stephen Olubusola Ilugbo (Indonesian Journal of Earth Sciences, 2021)
This research was carried out within Institute of Agriculture Research and Training Moor Plantation Ibadan, Southwestern Nigeria, with the aim to ascertain suitability of the proposed site for building construction and usage. The geophysical investigation involved three electrical resistivity techniques; Vertical Electrical Sounding (VES) using the Schlumberger configuration, 2D ERT and 2-D electrical imaging using Dipole-dipole electrode configuration. Two traverses were established E–W direction cutting across geologic strike with a distance of 80 m and of varying inter-traverse spacing. Eight (8) VES stations were occupied covering the entire study area for layer stratification and geoelectric parameters. The results were qualitatively and quantitatively interpreted and are presented as sounding curves and geoelectric sections. The 2-D imaging gave information on the subsurface characteristic in the area with generally low apparent resistivity indicating low competence material. The results obtained from the VES delineate three geoelectric units which comprise of the topsoil, weathered layer and fresh basement. The results from the VES were used to determine the second order parameters. The entire results correlate well with one another showing that all the techniques used were complemented. This study has further justified the need for geophysical site investigation as pre-condition before any construction to avoid problems of differential settlement. In determining of foundation material, topography elevation, clay content and the depth of weak zones should be put into consideration, since the depth of the weak zone is appreciably high.